Challenges of quality improvement in the healthcare of South Africa post-apartheid : a critical review - Maphumulo, Winnie T.; Bhengu, Busisiwe R. (Curationis (Pretoria), 2019)
Background: There is overwhelming evidence that the quality of health care in South Africa has been compromised by various challenges that impact negatively on healthcare quality. Improvement in quality care means fewer errors, reduced delays in care delivery, improvement in efficiency, increased market share and lower cost. Decline in quality health care has caused the public to lose trust in the healthcare system in South Africa. Objectives: The purpose of this study was to identify challenges that are being incurred in practice that compromise quality in the healthcare sector, including strategies employed by government to improve the quality of health delivery. Method: Literature search included the following computer-assisted databases and bibliographies: Medline (Medical Literature Online), EBSCOhost, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Google, Google Scholar and ScienceDirect. Furthermore, websites were used to source policy documents of organisations such as the National Department of Health in South Africa and the World Health Organization. Results: Seventy-four articles were selected from 1366 retrieved. These articles quantify problems facing quality care delivery and strategies used to improve the healthcare system in South Africa. Conclusion: The findings revealed that there were many quality improvement programmes that had been initiated, adapted, modified and then tested but did not produce the required level of quality service delivery as desired. As a result, the Government of South Africa has a challenge to ensure that implementation of National Core Standards will deliver the desired health outcomes, because achieving a lasting quality improvement system in health care seems to be an arduous challenge.